The Influence of Belief, Religiosity, and Service on the Interest of the Muslim Community in Paying Zakat at Lazismu, Pekalongan City - Siti Azzahrah; Moegiri Moegiri (Jurnal Hukum Khaira Ummah, 2026)
This study aims to analyze the influence of trust, religiosity, and service on the interest of the Muslim community in paying zakat through Lazismu Pekalongan City. This study uses a quantitative approach with a questionnaire method distributed to 100 respondents (muzakki), and analyzed using multiple linear regression with the help of IBM SPSS through validity tests, reliability, classical assumption tests, t tests, F tests, and coefficients of determination (R²). The results of the study indicate that partially trust and religiosity have a positive and significant effect on the interest in paying zakat with a significance value of 0.001 <0.05 each, while service has no significant effect with a significance value of 0.875 > 0.05. Simultaneously, the three variables have a significant effect on the interest in paying zakat with a significance value of 0.000 <0.05. The coefficient of determination (R²) value of 0.645 indicates that the variables of trust, religiosity, and service are able to explain the influence of 64.5% on the interest in paying zakat, while the remaining 35.5% is influenced by other factors outside this study, so it can be concluded that trust and religiosity are the main factors that influence the interest of the Muslim community in paying zakat through Lazismu Pekalongan City.